Rethinking COVID-19 and Beyond: Prevention, Remedies, and Recovery - Maffetone, Philip B.; Laursen, Paul B. (Frontiers in Public Health, 2022)
In a relatively short timeframe, millions of deaths and illnesses associated with COVID-19 have been reported, accompanied by substantial economic losses, and overall, negatively impacting society. This experience should serve as a wakeup call to those in public health and healthcare, along with politicians and citizens: COVID-19 is considered a predictable and preventable disaster. While various reactive responses to address the pandemic were implemented, some with adverse effects, proactive measures in the years before COVID-19 were neglected. Predominately this involved the development of a preventable overfat pandemic, which played a key role in both rising rates of chronic disease, the comorbidities that increase the risk for COVID-19, along with associated inflammation and malnutrition. This increased the risk of infection in billions of people worldwide, which, in essence, primed society for high rates of COVID-19 infection. Excess body fat evolves primarily from poor nutrition, particularly the overconsumption of sugar and other refined carbohydrates, which replace the vital nutrients needed for optimal immune function. Sugar and refined carbohydrates must be considered the new tobacco, as these foods are also devoid of nutrients, and underly inflammatory chronic diseases. A balanced diet of nutrient-dense wholefood must be emphasized to combat infectious and inflammatory diseases. Implementing proactive preventive lifestyle changes must begin now, starting with simple, safe, and inexpensive dietary modifications that can quickly lead to a healthier population.